Factors Influencing Early Marriage in Ponorogo, Indonesia: An Islamic Law Perspective - Dimas Adi Saputra; Muthoifin (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study analyzes the factors influencing early marriage in Ponorogo Regency, Indonesia, from an Islamic law perspective. Theoretical framework: This research is grounded in Islamic legal theory, particularly maqasid al-shariah, which emphasizes protection of religion, life, lineage, intellect, and property in regulating marriage practices. Literature review: Previous studies indicate that early marriage is influenced by cultural traditions, economic hardship, low educational attainment, religious interpretation, and unintended pregnancy, with a significant rise in dispensation cases reported by religious courts in Indonesia. Methods: This study employs a qualitative literature study approach using secondary data from academic journals, books, and official reports, following Mestika Zed's framework, without field data collection. Results: The findings show that early marriage in Ponorogo is mainly driven by out-of-wedlock pregnancy, followed by economic conditions, cultural norms, low education levels, personal willingness, and limited religious understanding, with consistently high dispensation cases recorded by the Religious Court. Implications: The study suggests the need for strengthened Islamic education, improved reproductive health awareness, stricter marriage dispensation evaluation, and enhanced community engagement to reduce early marriage rates. Novelty: This study integrates Islamic legal analysis with empirical trends from Religious Court data in Ponorogo, providing a contextual understanding of early marriage drivers rarely combined in previous literature. Furthermore, the persistence of early marriage in Ponorogo reflects a complex interaction between socio-cultural traditions, economic vulnerability, and limited access to comprehensive reproductive health education, while Islamic legal principles emphasize prevention of harm (darar) and protection of lineage (hifz al-nasl), suggesting that policy interventions should combine legal enforcement, community-based education, and strengthened coordination between religious institutions and government agencies to effectively reduce the rate of marriage dispensation cases among adolescents in the region through integrated Islamic socio-legal approaches. We recommend collaborative preventive strategies and policy reform urgently for sustainable social impact.